An unusual type of myeloid sarcoma localization following myelofibrosis: A case report and literature review. (2017) - Orofino, Nicola; Cattaneo, Daniele; Bucelli, Cristina; Pettine, Loredana; Fabris, Sonia; Gianelli, Umberto; Fracchiolla, Nicola Stefano; Cortelezzi, Agostino; Iurlo, Alessandra
Abstract: Myeloid Sarcoma (MS) is a rare malignancy that can present as an isolated disease or more frequently in association with or following acute myeloid leukemia or other myeloid neoplasms and rarely following myelofibrosis. Since molecular pathogenesis and prognostic factors of MS are not well understood, its prognosis remains poor even in the era of novel agents and target therapies. We report the case of a patient with MS following myelofibrosis with multiple subcutaneous, cutaneous and muscle localizations; the latter has been reported in the literature as anecdotal. In this way we aimed to enhance the understanding of this disease.